OPTIMALISASI PENGGUNAAN MEDIA AUDIO VISUALINTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN SISWAKELAS IX PADA MATA PELAJARAN AL-QUR’AN HADIST DIMADRASAH TSANAWIYAH AL- MUNAWWARAH KOTA JAMBI - Ines Oktavia Sari; Indah Nurul Hazairin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: Students’ limited understanding of the Qur’an and Hadith subject remains a common problem in madrasahs, particularly regarding the reading of gharib texts, which require conceptual understanding and strong reading skills. This study aims to optimize the use of interactive audiovisual media to improve ninth-grade students’ understanding of the Al-Qur’an and Hadith subject at MTs Al-Munawwarah in Jambi City. The study employed the Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles, encompassing the planning, implementation, observation, and reflection stages. The research subjects consisted of 23 ninth-grade students. Data collection techniques included observation, achievement tests, and documentation. The results showed that the use of interactive audiovisual media significantly improved students’ comprehension and learning outcomes. Student mastery rates increased from 17.39% in the pre-cycle phase to 65.22% in Cycle I and reached 86.95% in Cycle II. Students’ average scores also increased from 56.52 in the pre-cycle to 74.13 in Cycle I and 86.95 in Cycle II. Additionally, students’ activity levels, attention, and enthusiasm during learning showed positive improvements.